Diagnostic ability of SPECT-CT of Parathyroid Gland in correlation with different Biochemical Markers, BMD and USG of neck -Single Institute based Experience. (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: Detection of parathyroid adenoma or hyperplasia/ carcinoma by imaging is very challenging.The objective of this study was   to assess the imaging findings of  Single-Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) in neck and thorax  of patients and correlation with parathyroid hormone (PTH), Serum calcium, Inorganic phosphate(IP), Bone mineral density ( BMD) and also with  neck ultrasonography (USG of neck).Material & Methods: A total 75 study subjects were included in this retrospective study conducted from January 2011 to November 2018 in the Institute of Nuclear Medicine and Allied Sciences (INMAS), SSMCH, Mitford, Dhaka. All the patients came in this institute forparathyroid SPECT-CT were included for this study. SPECT-CT findings were compared with USG of neck, serum calcium, inorganic phosphate (IP) level and   BMD findings.Results: In this study 29 (38%) were male and 46(62%) were female. Mean PTH was 469±667 pg/ml, range 20-3110pg/ml, mean  serum calcium 9.8±1.5 mg/dl  with range 6.20 -14.30 mg/dl, mean IP3.00.8 mg/dl with range of 1.7 -4 mg/dl.  SPECT-CT positive patients were 32 (42.7%) and negative patients were 43 (53.3%). USG of neck positive patients were 21 (28%) and negative patients were 54 (72%).The PTH (r=0.53, p=0.0) serum Calcium (r=0.66,p= 0.0) positively correlate with SPECT-CT positive patients and negatively with IP level (r=-0.177, p> 0.05). Among 75 the patients, 44 patients had BMD report. 28 (63.6%) patients had SPECT –CT negative findings and 16 (36.4%) patients with positive SPECT-CT findings with P value